Grendel’s Mere, Beowulf’s Dive, and the Visio Sancti Pauli - Rafael Pascual (Revista Alicantina de Estudios Ingleses)
According to Hrothgar’s account of Grendel’s mere, every night one can see there fȳr on flōde, a phrase often translated as ‘fire on the water’. This fire, which the king describes as a nīðwundor (a dreadful wonder), has traditionally been seen by scholars as a supernatural phenomenon that contributes to the presentation of the place as eerie. Geoffrey Russom and Christopher Abram have taken an alternative view: they argue that the phrase means ‘fire in/within the water’ and interpret it in two different ways. Russom believes that Grendel’s mere is an entrance to hell, and that fȳr on flōde refers to gleams of infernal light showing through the water. Abram, on the other hand, thinks that it is a kenning-like expression to refer to light emanated from the treasures lying within the monsters’ hall. This essay agrees with them that the phrase means ‘fire in the water’, but it argues that the reference is to the ordinary fire burning within the hall (mentioned in 1516b). The essay proposes that the poet took the motif of the fiery river from a vernacular version of the Visio Sancti Pauli (long thought to be among the poet’s sources) and rationalized it as an ordinary fire misconstrued by Hrothgar as a supernatural wonder, thereby playing with the audience’s expectations. The piece concludes by exploring the implications of its argument for two long-standing interpretative cruces in the poem: Hrothgar’s gaze at the gigantic sword hilt and Beowulf’s supposed ability to dive for hours on end.